ECO-FRIENDLY LEACHING OF METALLIC SILVER WITH BORIC ACID: KINETICS STUDY - Boyrazli, Mustafa; Abdelraheem, Mohamed Taha Osman; Aydogan, Salih; Ali, Babiker; Mammadov, Kamil (Chem Soc Ethiopia, 2025)
This article discusses the kinetics of using a hydrogen peroxide solution to dissolve pure metallic silver in boric acid. The impact of temperature, rotation speed, hydrogen peroxide (H2O2) concentration, and boric acid concentration were investigated. The results indicate that silver dissolution rate and rotation speed have a positive relationship. Additionally, boric acid concentrations ranging from 0.10 to 0.40 M significantly enhance the dissolution process. The hydrogen peroxide concentration has no discernible influence on the rate of dissolution. While temperatures between 20 and 40 degrees C are beneficial, temperatures above 40 degrees C had the opposite effect and caused a layer of boron oxide (B2O3) to form. The activation energy was determined to be 30.49 kJ/mol.
Keywords: Silver; Dissolution; Hydrogen peroxide; Boric acid; Activation energy